Alternative dispute resolution: formation of the concept - Podkovenko, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article reveals the role and importance of alternative ways of resolving legal disputes and conflicts. The search for alternatives to state courts for resolving disputes is conditioned by a number of factors that vary according to the specific society, state, culture, legislation, the judicial system, the effectiveness of its work, the degree of development and the complexity of economic and other relations and other circumstances.